Pengaruh Gaya Kepemimpinan, Komunikasi Dan Kinerja Pengurus Terhadap Loyalitas Organisasi (Studi Pada Pengurus Organisasi Badan Eksekutif Mahasiswa Fakultas Ekonomi dan Bisnis Universitas Islam Malang) - Iwan Budianto; Muhammad Ridwan Basalamah; Nanik Wahyuningtyas (E-JRM : Elektronik Jurnal Riset Manajemen, 2023)
Abstract Organizational loyalty is the subject of this study, which examines the management of the Student Executive Board of the Faculty of Economics and Business, Islamic University of Malang. Its objective is to determine how organizational loyalty is affected by leadership style, communication, and management performance. The method of distributing questionnaires is used in this type of research, which is quantitative. The 68 respondents in this study were all administrators of BEM FEB 2021/2022, and the SPSS computer program was used to process the data. Validity and reliability requirements have been met by this study. The data in this study were analyzed using the classical assumption test, multiple linear regression, hypothesis testing, and coefficient of determination analysis. Organizational loyalty is the dependent variable in this study, while leadership style, communication, and management performance are the independent variables. Keywords: Organizational Loyalty, Leadership Style, Communication and Management Performance.